Formulation of Ready-to-Use Fish Food Based on Mackerel (Scomberomorus) and Catfish (Clarias gariepinus) - Ratna Komala Putri; Dias Indrasti; Puspo Edi Giriwono (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
This study developed Ready-to-Use Fish Food (RUFF) as a high-energy, high-protein recovery food for children under five with severe acute malnutrition, using mackerel and catfish powders as animal protein sources. Four RUFF variants were formulated with skim milk powder, mackerel powder, catfish powder, and a mixture of both fish powders. Nutritional analysis included moisture, ash, protein, fat, carbohydrates, and energy content, which were compared to Codex Alimentarius (CXG 95-2022) standards. Protein ranged from 2.31 to 4.61 g/100 kcal, fat from 5.64 to 6.25 g/100 kcal, carbohydrates from 6.79 to 9.44 g/100 kcal, and energy from 524 to 550.49 kcal/100 g, meeting FAO/WHO criteria for therapeutic foods. The sensory acceptability was assessed using a hedonic test with toddlers aged 2 to 5 years using a Balanced Incomplete Block Design. Scores ranged from 1 (like), 2 (neutral), and 3 (dislike), analyzed by ANOVA and Tukey’s test. The mixed fish powder variant had the least preference (mean score 2.08, neutral), while catfish, mackerel, and skim milk variants were liked (scores 1.23 to 1.83). Results confirm that these RUFF variants are nutritionally adequate and well accepted, supporting their use as an effective alternative to RUTF for malnourished toddlers.